PRESERVING THE PAST EMPOWERING THE FUTURE IN THE INTEGRATED CULTURAL HERITAGE TOURISM OF THE SEKARAN SITE MALANG - Irwan Yulianto (Universitas Dharmawangsa, 2026)
Sekaran Site, located in Pakis District, Malang Regency, is one of the cultural heritages that holds significant historical, archaeological, and tourism potential. This study aims to analyze the potential development of the Sekaran Site as an integrated tourism destination by examining its historical aspects, physical conditions, accessibility, and sustainable management strategies. A qualitative research method was employed, using data collection techniques such as field observation, in-depth interviews with stakeholders, and literature review. The findings reveal that the Sekaran Site offers main attractions in the form of ancient artifacts, unique local historical narratives, and the potential to be integrated into the Malang Regency heritage tourism route. However, challenges include limited supporting infrastructure, insufficient digital-based promotion, and the absence of optimal cross-sectoral collaboration schemes. This research contributes to the literature on cultural tourism management in Indonesia by proposing a development model based on the integration of attractions, amenities, accessibility, and community collaboration. The study highlights the importance of strengthening destination branding, providing interactive historical interpretation facilities, and implementing sustainable tourism principles. In addition, it emphasizes the role of local communities in co-creating value through participatory tourism management and knowledge sharing. Such involvement not only supports cultural preservation but also enhances visitors’ experiences. The findings are expected to serve as a reference for local governments, tourism stakeholders, and communities in optimizing the potential of the Sekaran Site as a leading tourism destination that preserves cultural heritage while simultaneously promoting local economic growth.